Peningkatan Mutu Madrasah melalui Modal Sosial - Ju’subaidi, Ju’subaidi (Nadwa, 2012)
This paper attempts to examine the important role of social capital in the meninges-forces madrasah education quality. Madrasah as national education subsystem has a heavy burden in carrying out the mandate of the law. The biggest problem is the activity of improving the quality of education that is determined by the achievement of the ultimate goal of education effectively and more efficiently. That goal is the realization of academic ability, moral and social. Structure and values of the communities around it is actually a social capital that should be used by the madrassa to improve the quality of education. Social capital is a means of achieving national education goals.